A discrete choice experiment on price and flavour effects on the appeal of nicotine products: a pilot study among young adults in Switzerland - Larissa Merz; Milo A. Puhan; Miquel Serra-Burriel (Swiss Medical Weekly)
AIMS: To explore the effects of prices and flavour availability on the appeal of different tobacco and nicotine products, including conventional cigarettes, Electronic Nicotine Delivery Systems (ENDS) and Heated Tobacco Systems (HTS) among an adult population in Switzerland.